PENGARUH PEMBERIAN BEBERAPA JENIS HIJAUAN TERHADAP PERFORMANS TERNAK KELINCI - Mas’ud, Chelry S; Tulung, Y. L. R.; Umboh, J.; Rahasia, C. A. (Universitas Sam Ratulangi, 2015)
THE FFECT OF SOME TYPES OF FORAGE FOR LIVESTOCK PERFORMANCE RABBIT. Rabbit productions may have considerable potential in developing counties as a means of converting forages and agricultural by product to meat. The present study was conductes to laborate leaves, and their combinations in the diets on rabbit performance. Twenty one 6-week old weaned rabbits, weighing 300-400 gramns were used in this trial. Animals were put in individual metabolic crates. A Completely Randomized Design with 7 treatments and 3 replications was used as an experimental design and Tukey test was employed to determine treatmen differences. Treatments were arranged as: R1 : carrot leaves + concentrate; R2 : kale leaves + concentrate; R3 : cabbage leaves + concentrate; R4 : carrot and cabbage leaves + concentrate; R5 : kale and cabbage leaves + concentrate; R6 carrot andÂ kale leaves; R7 : carrot + kale + cabbage leaves + concentrate. Parameters measured were; daily feed consumption, daily gain, and feed conversion ratio. Research result showed that treatments significantly affected daily feed consumption, daily gain, and feed convertion ration be concluded that the combination of carrot and cabbage leaves can support rabbit performance in the present study. Keywords : Rabbit, daily feed consumption, daily gain, feed convertion ratio.